(3ZQGFH GdZQQ hYQGFS GdacQ aj CMcGe GdfXQs - (3GHf YWjI GdMehjs
(3ChdgG (B:s
(3CeG HYO agPg QSGdI eJYdbI HGdfXQ ehOhYI faGFS GdacQ hLhGgQ GdOQQ efJNHI ef GdcJGH hGdSfI s
(3BNQgG (B:s
(3hGdMeO ddg GdPi gOGfG heG cfG dfgJOi dhdG Cf gOGfG Gddg Gddge Udi Ydi SjOfG eMeO hYdi Bdg hUMHg hSde s
(3GdfSNI HgG MhGTs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B_ (3GdbGgQI (B((3abg TGaYi (B- (3Mdje (B3) s
Keywords: (3Gdabg GdTGaYjs